Renal and Bleeding Complications in Critically Ill Covid-19 Patient-A Case Report - Pia, Masuma Islam; Islam, Tasbirul (Journal of Bangladesh College of Physicians and Surgeons, 2020)
The ongoing outbreak of Covid-19 presented with a wide variety of clinical manifestations. Apart from the common respiratory complications, acute renal impairment and bleeding complications on full anticoagulation has been also observed in some patients. Here we report a 67 year old male with COPD and CKD presented with symptoms of covid-19 and found ground glass opacity on CT scan and bibasilar opacity on chest X-ray, admitted to the hospital and he was initially stable after supportive management, discharged home on antibiotics but readmitted after 4 days with worsening shortness of breath, hypoxia, tachycardia (A-fib with Rapid Ventricular Response) and high ESR. He was started on High flow nasal cannula (HFNC), diltiazem, adenosine and antibiotics ultimately needed intubation. While he was on antibiotics, hydroxychloroquine, DVT prophylaxis and statin he developed septic shock two days after intubation. Next day he had to receive Continuous Renal Replacement Therapy (CRRT). He was placed on heparin infusion. With clinical improvement the patient was extubated to HFNC, but after one day of extubation he developed bradycardia, hypotension and gradually became unresponsive. He was given vasopressors and intubated again. CT scan showed retroperitoneal hematoma 10 x7 x 12 cm. His heparin was discontinued and was managed conservatively. With supportive treatment his clinical condition improved gradually and was extubated again. CRRT was switched from CVVH (Continuous Veno -Venous Hemofiltration) to HD and eventually he was discharged home. Clinicians should remain watchful at all stages of critical care management of COVID 19 because timely intervention and drug adjustment is lifesaving. J Bangladesh Coll Phys Surg 2020; 38(0): 136-140